Salidroside protects inner ear hair cells and spiral ganglion neurons from manganese exposure by regulating ROS levels and inhibiting apoptosis. (August 2019) - Ding, Xuerui; Wang, Weilong; Chen, Jiawei; Zhao, Qianqian; Lu, Peiheng; Lu, Lianjun
Highlights: Salidroside protected HCs, ANFs and SGNs from Mn exposure in a dose-dependent manner. The Mn-induced increase in the ROS level was attenuated by Salidroside. Salidroside suppresses Mn-induced activation of caspase-3. Mn induces TUNEL activation and protection by salidroside. Abstract: Manganese (Mn) is an essential cofactor for many enzymes and thus plays an important role in normal growth and development. However, persistent exposure to high Mn concentrations can result in deleterious effects on not only the central nervous system but also peripheral nerves, including nerves associated with the auditory system. Our initial research on cochlear organotypic cultures in vitro showed that N-acetylcysteine (NAC) clearly decreases Mn-induced losses in hair cells (HCs), auditory nerve ﬁbers (ANFs) and spiral ganglion neurons (SGNs) in a concentration-dependent manner. Salidroside (SAL) (p-hydroxyphenethyl-b-d -glucoside; C14H20O7), which is extracted from Rhodiola rosea L, has many pharmacological actions and antioxidative, antiaging, neuroprotective and anticancer effects. We hypothesized that SAL could also protect HCs, ANFs and SGNs from Mn injury. Cochlear organotypic cultures were treated with 1 mM Mn alone or combined with SAL (1–1000 μM). The neurofilament staining results showed that HCs, ANFs and SGNs were seriously damaged at high concentrations (100–1000 μM) but less damaged at low concentrations (1–10 μM). SAL may protect against 1 mM Mn-induced HC loss and axonal degeneration, suggesting that SAL could be a promising drug for clinical applications.